Performance analysis of thermoelectric generator using dc-dc converter with incremental conductance based maximum power point tracking - Twaha, Ssennoga; Zhu, Jie; Yan, Yuying; Li, Bo; Huang, Kuo (Elsevier, 2017)
Thermoelectric (TE) devices are regarded as alternative and environmentally friendly 7 for harvesting and recovering heat energy. Particularly, thermoelectric generators (TEGs) 8 are used for converting heat into electricity. One of the challenges behind TEG is that the 9 power generated is unstable and therefore needs proper power conditioning mechanism 10 before it is supplied to the load. Moreover, it is necessary to track the maximum power 11 point (MPP) at all times so that maximum power is always extracted from TEG devices. 12 The objective of this work is to analyse the performance of a dc-dc converter with 13 maximum power point tracking (MPPT) enabled by incremental conductance (IC) method. 14 The simplified model is used as the basis for TEG design while the dc-dc boost converter 15 is used for boosting and stabilising the power generated from TEG. The results of the IC 16 based MPPT approach have been compared with those of perturb and observe (P&O) based 17 MPPT from a previous researcher. The results indicate that the IC based MPPT approach 18 is able to track the MPP but with relatively lower efficiencies than the P&O based MPPT 19 method. The matching efficiency within a temperature range of 200oC– 300oC is in the 20 range of 99.92% - 99.95% for P&O and 99.46% - 99.97% for IC method. However IC 21 based MPPT method has higher voltage gain and converter efficiency than the P&O based 22 MPPT method. Therefore, dc-dc converters are able to improve the steady state 23 performance of TEG system as well as boosting the voltage to the desired level, hence 24 improving the overall performance of TEG system. Although both P&O and IC are two 25 classical algorithms that can be implemented to extract the maximum power from TEG, 26 the comparative study has established that P&O technique outperforms the IC method.